Stress triggers tree-growth rebound in global forests - Fang, Ouya; Zhang, Qi-bin (Agricultural and forest meteorology, 2024)
•Approximately 26 % of trees exhibited a growth rebound in the first year following stressful events.•The ring-width indices of rebounding trees is about 25 % higher than those of the non-rebounding trees in average.•Sixteen genera in global forests exhibited rebound effect, which varies depending on species and geographical location.•Old trees and slow-growing trees are more resilient in frequent stresses. Plants maintain their health through various ecological processes, among which resilience to external stresses has received increasing attention in recent years. By analyzing tree-ring data from 1762 sites, encompassing a total of 1,623,006 weak stresses (mean-2sd ≤ tree ring indices (TRI) < mean-sd) and 320,345 strong stresses (TRI < mean-2sd), we observed a significant growth increase following stresses for a subset of trees. We found that the growth increase was not a consequence of post-stress climate but an inherent property of trees’ response to stresses that could be called “rebound effect”. Across all the 16 genera studied, a similar proportion of trees, 26.23 % and 25.73 %, exhibits rebound effect in the first year after weak and strong stresses, respectively. The amplitudes of growth rebound, measured as the difference between the mean of ring-width indices in the rebounding year and the subsequent eight years, are 0.242 and 0.266 after weak and strong stresses, respectively. Conifers generally rebound at a higher proportion but to a lesser amplitude than broadleaves. Furthermore, a higher proportion and greater amplitude of rebound were observed in trees having longer age and slower growth. Our findings provide a new perspective of tree resilience to disturbances and shed insights into the processes of forest recovery after growth suppressions.